Neutrophil to lymphocyte ratio predicts intracranial hemorrhage after endovascular thrombectomy in acute ischemic stroke - Pikija, Slaven (J Neuroinflammation, 2018)
BACKGROUND: The development of intracranial hemorrhage (ICH) in acute ischemic stroke is associated with a higher neutrophil to lymphocyte ratio (NLR) in peripheral blood. Here, we studied whether the predictive value of NLR at admission also translates into the occurrence of hemorrhagic complications and poor functional outcome after endovascular treatment (EVT). METHODS: We performed a retrospective analysis of consecutive patients with anterior circulation ischemic stroke who underwent EVT at a tertiary care center from 2012 to 2016. Follow-up scans were examined for non-procedural ICH and scored according to the Heidelberg Bleeding Classification. Demographic, clinical, and laboratory data were correlated with the occurrence of non-procedural ICH. RESULTS: We identified 187 patients with a median age of 74 years (interquartile range [IQR] 60–81) and a median baseline National Institutes of Health Stroke scale (NIHSS) score of 18 (IQR 13–22). A bridging therapy with recombinant tissue-plasminogen activator (rt-PA) was performed in 133 (71%). Of the 31 patients with non-procedural ICH (16.6%), 13 (41.9%) were symptomatic. Patients with ICH more commonly had a worse outcome at 3 months (p = 0.049), and were characterized by a lower body mass index, more frequent presence of tandem occlusions, higher NLR, larger intracranial thrombus, and prolonged rt-PA and groin puncture times. In a multivariate analysis, higher admission NLR was independently associated with ICH (OR 1.09 per unit increase, 95% CI (1.00–1.20, p = 0.040). The optimal cutoff value of NLR that best distinguished the development of ICH was 3.89. CONCLUSIONS: NLR is an independent predictor for the development of ICH after EVT. Further studies are needed to investigate the role of the immune system in hemorrhagic complications following EVT, and confirm the value of NLR as a potential biomarker.